Pengukuran waktu baku dan analisis beban kerja pada Produk Insulation Pillows di PT XYZ - Perdiansyah, Muhammad Ilham; Ernawati, Dira (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
PT XYZ, is a construction and steel fabrication company that has contributed to various national and international projects. One of its products is insulation pillows, used in a wide range of industrial applications. The study aims to measure standard time and analyze workload in the production process of insulation pillows at PT XYZ. Standard time measurement was conducted using the Stopwatch Time Study method for five main production stages: Marking Cutting, bending, fit-up, assembling, and packing. The results indicate that the standard times for each process are as follows: Marking Cutting (35.46 minutes/unit), bending (19.26 minutes/unit), fit-up (110.50 minutes/unit), assembling (168.26 minutes/unit), and packing (117.83 minutes/unit). Workload analysis revealed that the assembling process has an excessive workload of 175%, necessitating the addition of one worker to achieve optimal workload distribution. These findings provide recommendations for workforce optimization in the production process to enhance efficiency and meet production targets